The Impact of Trade Prices on Employment and Wages in the United States - Hakura, Dalia (IMF Working Papers; Working Paper ;, 1997)
This paper investigates the sensitivity of sectoral employment and wages in the United States to changes in foreign trade prices for 1980-90. Previous studies have concentrated mainly on the impact of changes in import prices on employment and wage levels. This paper estimates the impact of changes in both import and export prices on employment and wages in each of 12 three-digit standard industrial classification (SIC) manufacturing sectors. The basic conclusion is that, for most sectors, changes in trade prices do not have significant effects on employment and wages, although they generally have a larger impact on employment than on wages.